2023
DOI: 10.1186/s12913-023-09254-5
|View full text |Cite
|
Sign up to set email alerts
|

Information and communication technology-based interventions for suicide prevention implemented in clinical settings: a scoping review

Abstract: Background A large number of information and communication technology (ICT) based interventions exist for suicide prevention. However, not much is known about which of these ICTs are implemented in clinical settings and their implementation characteristics. In response, this scoping review aimed to systematically explore the breadth of evidence on ICT-based interventions for suicide prevention implemented in clinical settings and then to identify and characterize implementation barriers and fac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 156 publications
0
9
0
Order By: Relevance
“…Without a careful investigation of the context, implementation strategies have often been mismatched with existing barriers in a given context [58,59]. As a prior work for this study, Shin et al [52] conducted a scoping review of ICTs (eg, apps) for suicide prevention that have been implemented in clinical settings and identified that barriers and facilitators collectively influence clinicians' capability, opportunity, and motivation to implement innovations. Therefore, implementation strategies must be tailored and multifaceted to simultaneously target these determinants of behavior change to maximize implementation [60].…”
Section: Problem and Rationale For This Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Without a careful investigation of the context, implementation strategies have often been mismatched with existing barriers in a given context [58,59]. As a prior work for this study, Shin et al [52] conducted a scoping review of ICTs (eg, apps) for suicide prevention that have been implemented in clinical settings and identified that barriers and facilitators collectively influence clinicians' capability, opportunity, and motivation to implement innovations. Therefore, implementation strategies must be tailored and multifaceted to simultaneously target these determinants of behavior change to maximize implementation [60].…”
Section: Problem and Rationale For This Studymentioning
confidence: 99%
“…Therefore, implementation strategies must be tailored and multifaceted to simultaneously target these determinants of behavior change to maximize implementation [60]. However, most of the reported implementation strategies focus on improving knowledge and building skills (ie, capability) without addressing clinicians' motivation and opportunity [52]. The fact that implementation strategies are often developed nonsystematically and do not match contextual implementation determinants is a consistently reported gap in the literature [61].…”
Section: Problem and Rationale For This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the technical aspects of developing, maintaining, and operating digital interventions have rarely been discussed [ 21 , 22 ]. Furthermore, there is a dearth of comprehensive research that adequately examines the implementation characteristics of ICT-based interventions in real-world settings, encompassing both the obstacles and factors that aid their implementation [ 23 , 24 ]. Ultimately, to support well-informed decision-making regarding the development of DSPSs, it is vital to establish whether ICT-based suicide prevention strategies are effectively reaching various target audiences or whether they are reaching the same individuals through different means.…”
Section: Introductionmentioning
confidence: 99%